Viral hepatitis in patients on hemodialysis. Issue 3 (11th May 2020) - Winston, Anna; Wurcel, Alysse G.; Gordon, Craig; Goyal, Nitender
Abstract: Hepatitis B and hepatitis C (HCV) prevalence are higher in people on hemodialysis (HD) than the general population. Through implementation of prevention interventions including vaccines, serologic screening, and post‐exposure management, transmissions linked to HD have decreased dramatically. In this manuscript, we review epidemiology of viral hepatitis, summarize current screening and vaccine recommendations, and appraise the available data about efforts to decrease incidence within HD facilities, including isolation of people with viral hepatitis within HD units. Also included is a discussion of the highly effective all‐oral HCV treatment options and treatment for HCV in people awaiting kidney transplant.